2019
DOI: 10.33338/ef.84673
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of common ground beetles (Coleoptera: Carabidae) along an urbanisation gradient near Sorø, Zealand, Denmark

Abstract: The seasonal activity of six carabid species (Nebria brevicollis, Carabus nemoralis, C. hortensis, C. coriaceus, Pterostichus melanarius and Abax parallelepipedus) was studied along an urbanisation gradient (rural forest – suburban forest – forest fragments in urban park) in Sorø, Denmark, during April–October 2004 and 2005.Two groups were identified: 1) Species with constant seasonality, in which seasonal activity profiles did not differ along the gradient (C. hortensis, C. coriaceus, and A. parallelepipedus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The second group consists of species whose activity pattern varied remarkably among the differently urbanized habitats. Adults of C. nemoralis appeared about 4 weeks earlier in the urban forest patches than the rural ones and showed a steep autumn activity increase in the rural habitats [47,48].…”
Section: Effects Of Urbanization At the Population Levelmentioning
confidence: 95%
See 1 more Smart Citation
“…The second group consists of species whose activity pattern varied remarkably among the differently urbanized habitats. Adults of C. nemoralis appeared about 4 weeks earlier in the urban forest patches than the rural ones and showed a steep autumn activity increase in the rural habitats [47,48].…”
Section: Effects Of Urbanization At the Population Levelmentioning
confidence: 95%
“…Changes in microclimate associated with urbanization (e.g., the urban "heat island" effect) could influence the activity start or change the timing of activity peaks of urban populations. Studies on seasonality of ground beetles along a Danish urbanization gradient identified two main groups [47,48]. The first one includes species whose activity profiles did not differ between rural and urban habitats (N. brevicollis with bimodal and P. melanarius with unimodal activity pattern).…”
Section: Effects Of Urbanization At the Population Levelmentioning
confidence: 99%
“…The second maximum of the activity of C. nemoralis occurs in October, which is outside the period of our study. The course of the second maximum is influenced by temperature, where, in warmer years, newly hatched individuals are more active in autumn [31]. This situation occurred in the autumn of 2018, where the species was active at three study plots (both forest stands and the R1 recovering forest stand, Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…Adults remain active until about July, then start aestivation during August and September. The work in [31] states that C. nemoralis is a species that reproduces in spring and that its seasonal activity features two peaks. The second maximum of the activity of C. nemoralis occurs in October, which is outside the period of our study.…”
Section: Discussionmentioning
confidence: 99%
“…For identification, keys by Lindroth (1985Lindroth ( , 1986 and Hůrka (1996) were used. The total material collected was 10314 individuals of 43 species in 2004, and 4961 individuals of 38 species in 2005 (Elek et al 2017).…”
Section: Methodsmentioning
confidence: 99%